Evaluasi Rasionalitas Penggunaan Antibiotik Pada Pasien dengan Demam Tifoid di Rumah Sakit X di Surakarta - Adhi W. Amrullah; Rolando Rahardjoputro; Atiek Murharyati; Avianti Eka Dewi Aditya Purwaningsih (Fakultas Farmasi Universitas Setia Budi, 2024)
The bacterium Salmonella typhi is the cause of a systemic infection known as typhoid fever. These bacteria usually enter through contaminated food or drink. To treat typhoid fever, antibiotics must be given as rationally as possible to achieve ideal therapeutic goals. An understanding of various aspects of an infectious disease should be used to plan the use of antibiotics. This understanding must also consider the pharmacokinetics and pharmacodynamics of the antibiotic to be used as well as individual resistance, virulence and microorganisms. The development of antibiotic-resistant bacteria is the worst effect of irrational use of antibiotics. In this study, the Gyssens method was used to analyze the rationality of antibiotics. This observational descriptive study also uses a cross-sectional approach. Data was collected through a retrospective search of medical records in the medical records section of